Immediate effects of acupuncture on biceps brachii muscle function in healthy and post-stroke subjects - Fragoso Ana; Ferreira Arthur S (BMC, 2012)
Abstract Background The effects of acupuncture on muscle function in healthy subjects are contradictory and cannot be extrapolated to post-stroke patients. This study evaluated the immediate effects of manual acupuncture on myoelectric activity and isometric force in healthy and post-stroke patients. Methods A randomized clinical trial, with parallel groups, single-blinded study design, was conducted with 32 healthy subjects and 15 post-stroke patients with chronic hemiparesis. Surface electromyography from biceps brachii during maximal isometric voluntary tests was performed before and after 20-min intermittent, and manual stimulation of acupoints Quchi (LI11) or Tianquan (PC2). Pattern differentiation was performed by an automated method based on logistic regression equations. Results Healthy subjects showed a decrease in the root mean-squared (RMS) values after the stimulation of LI11 (pre: 1.392 ± 0.826 V; post: 0.612 ± 0.0.320 V; P = 0.002) and PC2 (pre: 1.494 ± 0.826 V; post: 0.623 ± 0.320 V; P = 0.001). Elbow flexion maximal isometric voluntary contraction (MIVC) was not significantly different after acupuncture stimulation of LI11 (pre: 22.2 ± 10.7 kg; post: 21.7 ± 9.5 kg; P = 0.288) or PC2 (pre: 18.8 ± 4.6 kg; post: 18.7 ± 6.0 kg; P = 0.468). Post-stroke patients did not exhibit any significant decrease in the RMS values after the stimulation of LI11 (pre: 0.627 ± 0.335 V; post: 0.530 ± 0.272 V; P = 0.187) and PC2 (pre: 0.601 ± 0.258 V; post: 0.591 ± 0.326 V; P = 0.398). Also, no significant decrease in the MIVC value was observed after the stimulation of LI11 (pre: 9.6 ± 3.9 kg; post: 9.6 ± 4.7 kg; P = 0.499) or PC2 (pre: 10.7 ± 5.6 kg; post: 10.2 ± 5.3 kg; P = 0.251). Different frequency of patterns was observed among healthy subjects and post-stroke patients groups (χ2 = 9.759; P = 0.021). Conclusion Manual acupuncture provides sufficient neuromuscular stimuli to promote immediate changes in motor unit gross recruitment without repercussion in maximal force output in healthy subjects. Post-stroke patients did not exhibit significant reduction on the myoelectric activity and maximal force output after manual acupuncture and needs further evaluation with a larger sample. Trial registration Brazilian Clinical Trials Registry RBR-5g7xqh.